Indistinguishable Participants - Elbourne, Paul (Proceedings of the Amsterdam Colloquium, 2003)
This paper addresses the 'problem of indistinguishable participants' posed for E-type analyses of donkey anaphora by Kamp. Sentences like If a bishop meets a bishop, he blesses him seem to be impossible to analyze in an E-type theory, because there are no definite descriptions that can serve as denotations for he and him, since the participants introduced are indistinguishable. The E-type analysis proposed here differentiates the two participants by making reference to the structure of the situations in which they are embedded. Meanwhile, previously neglected data show that dynamic semantics theories encounter problems with indistinguishable participant sentences, meaning that the E-type analysis with situation semantics is empirically superior to dynamic theories in this area.